A holistic and sustainable approach to public health staffing and workforce development - Mui, Paulani; Maiorana, Ruth; Resnick, Beth (Frontiers in Public Health, 2025)
Public health in the United States faces a continuous cycle of “neglect, panic, repeat.” As seen with 9/11, H1N1, and COVID-19, public health emergencies create a flurry of attention and resources, but once the crisis passes, focus quickly shifts to other matters until the next emergency, when the cycle repeats. This leaves the nation's public health system chronically under-resourced and ill-equipped to respond, resulting in a strained workforce that must remain nimble. Maintaining responsiveness to community needs requires a sustainable system with adequate worker supports. This perspective discusses findings from an assessment of short-term COVID-19 investments on long-term U.S. public health workforce needs, highlighting the need for a holistic approach to staffing and workforce development. Temporary staffing addressed immediate response needs, but presented challenges such as difficulties transitioning temporary staff into permanent roles and cohesively integrating temporary staff into ongoing agency operations, which often inadvertently increased administrative burdens on existing staff, exacerbating burnout and dampening morale. Ensuring a sustainable workforce necessitates innovative recruitment and retention strategies. Recommended strategies include holistic recruitment efforts in collaboration with community and academic partners, enhanced leadership training, staff compensation reviews, flexible work arrangements, and worker wellbeing initiatives. These findings guided the creation of the Putting Our People First Discussion Guide to empower agencies to engage workers in collective dialogue to improve workforce mental health, wellbeing, and retention. Bolstering a culture of worker wellbeing and retention alongside sustained funding and infrastructure is critical for the nation's public health agencies to effectively address current and future challenges.